2019
DOI: 10.31234/osf.io/fa9wr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Muscle And Fat Aftereffects And The Role Of Gender: Implications For Body Image Disturbance

Abstract: Body image disturbance – a cause of distress amongst the general population and those diagnosed with various disorders – is often attributed to the media’s unrealistic depiction of ideal bodies. These ideals are strongly gendered, leading to pronounced fat concern amongst females, and a male preoccupation with muscularity. Recent research suggests that visual aftereffects may be fundamental to the misperception of body fat and muscle mass – the perceptual component of body image disturbance. This study sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Whether or not adaptation is relevant to cases such as these has yet to be determined, but even if it is not, this technique remains an invaluable non-invasive method of probing the brain mechanisms underlying body perception. So far, adaptation studies have revealed these mechanisms to be high level (Hummel et al, 2012b ; Brooks et al, 2018 ), and selective for identity (Brooks et al, 2016 ) and gender (Brooks et al, 2019 , 2020a ), yet they generalize across race (Gould-Fensom et al, 2019 ). There also appear to be independent neural populations responsible for the perception of fat and muscle mass (Sturman et al, 2017 ; Brooks et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not adaptation is relevant to cases such as these has yet to be determined, but even if it is not, this technique remains an invaluable non-invasive method of probing the brain mechanisms underlying body perception. So far, adaptation studies have revealed these mechanisms to be high level (Hummel et al, 2012b ; Brooks et al, 2018 ), and selective for identity (Brooks et al, 2016 ) and gender (Brooks et al, 2019 , 2020a ), yet they generalize across race (Gould-Fensom et al, 2019 ). There also appear to be independent neural populations responsible for the perception of fat and muscle mass (Sturman et al, 2017 ; Brooks et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Viewing of motion in a consistent direction (e.g., the downward motion of a waterfall) for a sustained period (known as adaptation) causes subsequently viewed stationary objects (e.g., nearby rocks) to appear to move upwards. While many adaptation effects concern other basic stimulus properties such as color (Helmholtz, 1924 ) or line orientation (Gibson and Radner, 1937 ), aftereffects also apply to more complex stimulus attributes such as the configuration of facial features (Gwinn and Brooks, 2013 , 2015a , b ), or the adiposity or muscularity of human bodies (Sturman et al, 2017 ; Brooks et al, 2020a ). In psychophysical studies of adaptation, experimenters assume that the perceptual representation of the currently viewed stimulus becomes biased and that the stored representation against which it is implicitly being compared (e.g., stationary rocks, an average face, or a stored representation of one's own body) is veridical.…”
Section: Conceptual Distinctions and Models Of Body Representationmentioning
confidence: 99%
“…Whether visual adaptation underlies the BSSM components of these different conditions could be explained by a difference in the susceptibility of male and female observers to visual aftereffects of fat and muscle or a difference in the adaptability of the mental representations of male or female bodies for fat versus muscle. However, a recent investigation showed no differences between the magnitude of fat or of muscle aftereffects for men versus women regardless of whether analyses compared effects across the gender of observers or across the gender of body stimuli (Brooks, Keen, et al, 2019). 3 Even so, this result does not preclude the influence of adaptation in eating disorders or MD.…”
Section: Pumping Irony: Why Visits To the Gym Can Make Your Muscles Lmentioning
confidence: 99%
“…However, adaptation to wide and narrow black rectangles caused no perceptual distortion for subsequently viewed bodies, suggesting that body-width adaptation is not a low-level effect of width in general but a high-level aftereffect specific to body shape. Furthermore, many demonstrations of body aftereffects allow free eye movements (Brooks et al, 2016; Brooks, Baldry, et al, 2019; Brooks, Keen, et al, 2019; Glauert et al, 2009; Hummel, Grabhorn, & Mohr, 2012; Hummel, Rudolf, et al, 2012; Mohr et al, 2016; Stephen et al, 2016; Sturman et al, 2017; Winkler & Rhodes, 2005) rather than enforcing strict fixation in a given image location (as in the low-level color aftereffect in Fig. 1).…”
Section: Is the High-level Whole More Than The Sum Of Its Low-level Pmentioning
confidence: 99%
“…Weight misperception, a perceptual aspect of body image relating to over-or under-estimation of weight, is a separate construct from body dissatisfaction [15]. It is, however, unclear whether weight misperception is more common in females than males adolescents and vice versa [16][17][18]. Salient influences include unrealistic and idealised images of body size in print media, television and social media, cultural ideals and beliefs about body size, and identity development [14].…”
Section: Introductionmentioning
confidence: 99%